Histopathological spectrum of skin diseases in a tertiary skin health and referral centre (Journal of Pathology of Nepal, 2019)
Background: Skin diseases are very much prevalent in the developing countries. The pattern of skin diseases varies from country to country and even region to region within a country. The histological diagnosis is used by clinicians to aid in the management of patients & most appropriate clinical interventions.Materials and methods: The study included a total of 1040 skin biopsies from January 2016 to December 2018 in the department of pathology, DI skin health and referral centre, Kathmandu, Nepal.Results: The majority of the patients were in the age group of 31-40 years. The most common skin disease is non-infectious vesicobullous and vesicopustular disease (28.6%), followed by non-infectious erythematous papular and squamous disease (25.9%). The most common vesicobullous disease is spongiotic dermatitis (84.8%). Erythema dyschromicum perstans (31.8%) is the commonest non-infectious erythematous papular and squamous disease. The most common microbial disease is fungal infection, followed by leprosy. Among the neoplastic diseases of skin, tumors of epidermis are commonest diseases and the most common epidermal tumor is basal cell carcinoma. The commonest tumor of skin is melanocytic nevus.  The most frequent site is upper extremities.Conclusions: Eczema is predominating non-infectious vesicobullous and vesicopustular disease.  A relatively higher, prevalence of fungal infections was observed. Basal cell carcinoma is the commonest epidermal tumor and melanocytic nevus is commonest of all skin tumors.